2020
DOI: 10.1002/iub.2281
|View full text |Cite
|
Sign up to set email alerts
|

Various forms of HIF‐1α protein characterize the clear cell renal cell carcinoma cell lines

Abstract: Renal cell carcinoma (RCC) represents around 2-3% of all malignancies diagnosed in adult patients. Most frequent (around 70-80% cases) and the most aggressive subtype is clear cell RCC (ccRCC). Mutations in VHL (von Hippel Lindau) gene, characteristic for this cancer type, lead to altered activity of the trimeric VBC (pVHL-elongin B-C) complex and consequently to HIF-1α stabilization. In this study, we present results of exhaustive investigation of HIF-1α alternative transcript variants abundance in A498, CAKI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 31 publications
2
10
0
Order By: Relevance
“…Even though there was a clear increase in HIF1A expression in the resistant clones of 786-O and Caki-1 cells (Figure 5; Table 3), the HIF1α protein was not detected in these cell lines (Figure 6; Table 4). This is consistent with previous studies, that have shown a lack of protein expression in 786-O cells due to mutations [41,42], and even though Caki-1 cells do encode the intact HIF1A gene, the protein is only expressed under hypoxic conditions [43]. The fact that the HIF1A transcript, but not the protein, is induced in these cell lines could have functional significance in the resistance mechanism, as several long non-coding RNAs (lncRNAs) are encoded within this gene [44,45], and this is an area we are currently investigating.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Even though there was a clear increase in HIF1A expression in the resistant clones of 786-O and Caki-1 cells (Figure 5; Table 3), the HIF1α protein was not detected in these cell lines (Figure 6; Table 4). This is consistent with previous studies, that have shown a lack of protein expression in 786-O cells due to mutations [41,42], and even though Caki-1 cells do encode the intact HIF1A gene, the protein is only expressed under hypoxic conditions [43]. The fact that the HIF1A transcript, but not the protein, is induced in these cell lines could have functional significance in the resistance mechanism, as several long non-coding RNAs (lncRNAs) are encoded within this gene [44,45], and this is an area we are currently investigating.…”
Section: Discussionsupporting
confidence: 93%
“…The fact that the HIF1A transcript, but not the protein, is induced in these cell lines could have functional significance in the resistance mechanism, as several long non-coding RNAs (lncRNAs) are encoded within this gene [44,45], and this is an area we are currently investigating. Although A498 cells also contain a mutated HIF1A gene, the HIF1α protein is expressed constitutively under normoxic conditions due to defective VHL [43]. We observed that HIF1α expression was down-regulated in A498-resistant clones, a characteristic that was previously described to be the result of sunitinib-associated proteosome degradation [41].…”
Section: Discussionsupporting
confidence: 54%
“…Cancer holds the top second rank when it comes to deadly disease of today's human population in entire Europe (Liu et al, 2019;Rutz et al, 2019). Among the 10 common death-causing cancers, kidney cancer is one of the debilitating health problems world wide bannering RCC as the most commonly known renal malignancy (Xu et al, 2020;Swiatek et al, 2020). Couple of years ago, 1.8 crore (18 million) new cancer cases were diagnosed globally.…”
Section: Introductionmentioning
confidence: 99%
“…1A ). 786O RCC cells were chosen because they were shown to resemble ccRCC including the underlying VHL mutation [ 34 , 35 ]. After 6–8 hours allowing the cancer cells to adhere, we then coated well B with a thick layer of Matrigel ( Fig.…”
Section: Resultsmentioning
confidence: 99%